Infinite Teaching (R) In Collection and (R*) By Allegory and Conformity - Ahmad hedayatpanah shaldehi; Marziyeh hedayatpanah shaldehi; Kolachahi Sabet Mohammad Taghi; Mohammad Saeed hedayatpanah shaldehi, (Indian Journal of Advanced Mathematics (IJAM), 2024)
In given work a scientific base compatibility of polymers, produced by industry have been studied by revealing of thermodynamically regularities of polymer mixtures. The most significant thermodynamic regularities of the mixtures of polyolefin , produced by industry and heterochained polymers have been revealed and on this base the scientific bases of their compatibility have been developed for creation of multicomponent compositional materials with given complex of operating properties. Key words: polymer-polymer mixtures, chlorinated polyethylene (CPE), polymethylmetaacrylate (PMMA), polyethylene of low density (PELD), chlorcarboxylated polyethylene of low density (CCPE) chlorinated PELD (CPE), polyvinyl chloride (PVC), criteria of compatibility, chlorination, upper and lower critical temperature, specific holding of volume, Qibbs mixing energy, parameter of solubility, distribution of macromolecules, chlorine-chlorocontaining polymers, polar groups, thermodynamically compatibility, sorbate, gas-carrier.